Econometric analysis of the relationship between vaccination against COVID-19 and its occurrence in population - Shaibaneev, Roman (2023)
Over the whole COVID-19 pandemic the efficiency of vaccination was doubted by a large group of people. It was even thought that they are more harmful for people who took them. In this bachelor thesis I try to investigate the relationship between given vaccine doses and two variables - the ratio of deaths and recovered from the decease and its death rate. I try to estimate this effects by developing an ARDL model to deal with autocorrelation. I found a significantly negative total effect of the vaccines on the variables, whereas a more detailed analysis showed negative and significant effect on the variables from vaccine doses given in recent 3 months and also 9 months up until year. Also, logarithmic transformation does not create drastic changes in estimates having a little better residuals.